GE_GERICHTE C/26040/2016 vom 14. Januar 2020 - GE Cour de justice (2020)
ASSOCIATION;MANDAT;HONORAIRES;POUVOIR DE REPRÉSENTATION;PRINCIPE DE LA BONNE FOI;ABUS DE DROIT | CC.55; CC.69; CC.32.al1; CC.2.al1; CC.2.al2